Objektinių sakinių nominalizacija lietuvių ir anglų kalbose - Valeika, Laimutis (Kalbotyra, 1976)
An attempt is made to describe the nominalising transformations of objective sentences in Lithuanian and English. The nominalising properties of an objective sentence are mostly determined by its semantics. The most productive in Lithuanian and English are sentences containing action verbs. Two-constituent nominalisations generated by objective sentences may be ambiguous. The ambiguity is generally resolved by the context. Apart from the context, morphological (in Lithuanian) and syntactical (in English) means may be used.